Transcripts of internal messages from British military forces and the Royal Irish Constabulary - Irish Volunteers. Cork Brigade; O'Donoghue, Florence, 1895-1967; Great Britain. Army; Irish Republican Army. Southern Command, 1st (1921)
Includes related correspondence between I.R.A. Southern Division Intelligence Officers, some manuscript notes and annotations and general intelligence information.
Keywords: Royal Irish Constabulary; Great Britain. -- Army; Ireland -- History -- War of Independence, 1919-1921; Ireland -- History -- 1910-1921